2005
DOI: 10.1186/cc3904
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Traditional teaching suggests that corticosteroids should be avoided during acute infectious episodes for fear of compromising the immune response. However, the outcome benefit shown through steroid administration in early septic shock implies this paranoia may be misplaced. We therefore performed a systematic review of the literature to identify the current strength of evidence for the use of corticosteroids in specified infections, and to make appropriate graded recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 82 publications
0
12
0
3
Order By: Relevance
“…Currently, neuroinflammatory diseases such as meningitis are treated with corticosteroids in combination with antibacterial, antiviral, or antifungal agents (Aberdein and Singer, 2006; Hoffman and Weber, 2009). Corticosteroids have both anti-inflammatory and immunosuppressive properties and treatment with these agents has been shown to reduce the risk of hearing loss and mortality due to meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, neuroinflammatory diseases such as meningitis are treated with corticosteroids in combination with antibacterial, antiviral, or antifungal agents (Aberdein and Singer, 2006; Hoffman and Weber, 2009). Corticosteroids have both anti-inflammatory and immunosuppressive properties and treatment with these agents has been shown to reduce the risk of hearing loss and mortality due to meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids have been used for more than 60 years as adjunctive treatments of infections to mitigate local and systemic inflammatory responses. ( 20 ) These drugs are commonly used among critically ill patients, and a significant number of studies have demonstrated the benefits of using corticosteroids for patients in septic shock because they are associated with initial shock reversal, the mitigation of systemic inflammatory response indicators, and significant decreases in mortality. ( 21 , 22 )…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although long-term corticosteroid use with its attendant immunosuppression could increase the risk for abscess formation, a short course is unlikely to have the same effect. [4][5][6] The diagnosis of iliopsoas abscess can be difficult to make, and delays in diagnosis can result in sepsis and organ failure and are known to increase mortality. 2,3,7 Hip pain with impaired flexion and antalgic gait are characteristic complaints associated with iliopsoas abscesses and can serve as diagnostic clues.…”
Section: Discussionmentioning
confidence: 99%